Hindu residents' satisfactions on residential unit spatial layout of low-cost flat housing - Mat Raschid, Mohammad Yazah; Sharif, Roslina; Ooi, Siew Choong (Faculty of Design & Architecture, Universiti Putra Malaysia, 2015)
Religious and cultural considerations of specific communities are usually overlooked in the design of low-cost flats (LCF) in Malaysia, likely due to a poor understanding of religious-cultural needs. The result is a spatial layout that is generic and purely functional, in which Hindu households are expected to be experiencing some degree of dissatisfaction, as well as emotional and psychological stress. The research methodology is a phenomenological study of interviews with 30 Hindu households in LCFs around Puchong, Selangor. The results indicate that Hindu residents make do with the accommodations given as they have few other housing choices. Improvements can be made, however, to the design of LCFs to enhance the living experience of Hindu families and improve residential satisfaction.